Sex ratio and relatedness in the Griffon vulture (Gyps fulvus) population of Serbia - Slobodan Davidović; Saša Marinković; Irena Hribšek; Aleksandra Patenković; Marina Stamenković-Radak; Marija Tanasković (PeerJ, 2022)
Background Once a widespread species across the region of Southeast Europe, the Griffon vulture is now confined to small and isolated populations across the Balkan Peninsula. The population from Serbia represents its biggest and most viable population that can serve as an important reservoir of genetic diversity from which the birds can be used for the region’s reintroduction programmes. The available genetic data for this valuable population are scarce and as a protected species that belongs to the highly endangered vulture group, it needs to be well described so that it can be properly managed and used as a restocking population. Considering the serious recent bottleneck event that the Griffon vulture population from Serbia experienced we estimated the overall relatedness among the birds from this population. Sex ratio, another important parameter that shows the vitality and strength of the population was evaluated as well. Methods During the annual monitoring that was performed in the period from 2013–2021, we collected blood samples from individual birds that were marked in the nests. In total, 169 samples were collected and each was used for molecular sexing while 58 presumably unrelated birds from different nests were used for inbreeding and relatedness analyses. The relatedness was estimated using both biparentally (10 microsatellite loci) and uniparentally (Cytb and D-loop I of mitochondrial DNA) inherited markers. Results The level of inbreeding was relatively high and on average it was 8.3% while the mean number of relatives for each bird was close to three. The sex ratio was close to 1:1 and for the analysed period of 9 years, it didn’t demonstrate a statistically significant deviation from the expected ratio of 1:1, suggesting that this is a stable and healthy population. Our data suggest that, even though a relatively high level of inbreeding can be detected among the individual birds, the Griffon vulture population from Serbia can be used as a source population for restocking and reintroduction programmes in the region. These data combined with previously observed genetic differentiation between the populations from the Iberian and Balkan Peninsulas suggest that the introduction of foreign birds should be avoided and that local birds should be used instead.